Lactobacillus rhamnosus GR-1 Alleviates Escherichia coli-Induced Inflammation via NF-κB and MAPKs Signaling in Bovine Endometrial Epithelial Cells - Liu, Jiawei; Feng, Xiaowei; Li, Botong; Sun, Yan; Jin, Tianxiong; Feng, Mingque; Ni, Yaodi; Liu, Mingchao (Frontiers in Cellular and Infection Microbiology, 2022)
Escherichia coli counts as a major endometritis-causing pathogen among dairy cows, which lowered the economic benefits of dairy farming seriously. Probiotic consumption has been reported to impart beneficial effects on immunomodulation. However, the inflammatory regulation mechanism of probiotics on endometritis in dairy cows remains unexplored. The current work aimed to clarify the mechanism whereby Lactobacillus rhamnosus GR-1 (L. rhamnosus GR-1) resists bovine endometrial epithelial cells (BEECs) inflammatory injury induced by E. coli. The model of cellular inflammatory injury was established in the BEECs, which comes from the uterus of healthy dairy cows using E. coli. The outcome of L. rhamnosus GR-1 addition on inflammation was evaluated in BEECs with E. coli-induced endometritis. The underlying mechanisms of anti-inflammation by L. rhamnosus GR-1 were further explored in E. coli-stimulated BEECs. In accordance with the obtained results, the use L. rhamnosus GR-1 alone could not cause the change of inflammatory factors, while L. rhamnosus GR-1 could significantly alleviate the expression of E. coli-induced inflammatory factors. Based on further study, L. rhamnosus GR-1 significantly hindered the TLR4 and MyD88 expression stimulated by E. coli. Moreover, we observed that in BEECs, L. rhamnosus GR-1 could inhibit the E. coli-elicited expressions of pathway proteins that are associated with NF-κB and MAPKs. Briefly, L. rhamnosus GR-1 can effectively protect against E. coli-induced inflammatory response that may be closely related to the inhibition of TLR4 and MyD88 stimulating NF-κB and MAPKs.